Thoracolumbar fractures without neurological deficits: is CT scan and MRI necessary? - Zakaria@Mohamad, Zamzuri (2016)
Plain radiograph is an essential investigation in diagnosing patients who have an injury to the thoracolumbar spine. The earlier classification of thoracolumbar fractures was mainly based on plain radiographs where the bony structures or injury can clearly be identified. Later CT scan becomes more important in the assessment of thoracolumbar injury where the spinal osseo-ligamentous injury can clearly be identified and provides more information for patient management.